Comprehensive economic analysis of PV farm -A case study of Alkarsaah PV farm in qatar - Alashqar, Mohamed; Xue, Ying; Yang, Conghuan; Zhang, Xiao-Ping (Frontiers in Energy Research, 2022)
Countries around the world are rapidly deploying renewable energy generation to reduce carbon emissions. Countries in the Gulf Cooperation Council (GCC) are investing heavily in PV generation due to their rich solar resources. As PV technology becomes more mature, future PV developments will largely depend on the cost of the PV generation but there is currently very limited published work that shows a detailed design and in particular the economic analysis of large-scale PV farms. Therefore, this paper uses the Qatar’s first PV farm, the 800MWp Alkarsaah PV farm as a case study to explain the design considerations and especially the economic benefits of large-scale PV farms. Economic comparisons will be made with the most efficient CCGT (combined cycle gas turbine) plants in the network to highlight the economic benefits of PV farms. The results show that the Levelized cost of electricity (LCOE) for this PV farm is 14.03/MWh, much lower than the LCOE of 39.18/MWh and 24.6/MWh from the most efficient CCGTs in the network, highlighting the significant economic benefits of developing PV farms in a low carbon power networks in the future.